The Prediction Of Athletic Coping Skills Inventory, Leg Muscle Strength, Agility, Torso Flexibility, Eye-Foot Coordination, Leg Muscle Power With Idan Dollyo Chagi Tae Kwon Do Kyorugi Learning Result (Correlational Study on Player Tae Kwon Do 15-20 Year Age Group Class Under 54 Kilogram at Banyumas District) - Singgih Yoga Putranto; Agus Kristiyanto; Sapta Kunta Purnama (Kazimierz Wielki University, 2019)
This research aims to find out: (1) the prediction of athletic coping skills inventory with the idan dollyo chagi tae kwon do kyorugi learning result, (2) the prediction of leg muscle strength with the idan dollyo chagi tae kwon do kyorugi learning result, (3) the prediction of agility with the idan dollyo chagi tae kwon do kyorugi learning result, (4) the prediction of torso flexibility with the idan dollyo chagi tae kwon do kyorugi learning result, (5) the prediction of eye-foot coordination with the idan dollyo chagi tae kwon do kyorugi learning result, (6) the prediction of leg muscle power with the idan dollyo chagi tae kwon do kyorugi learning result, (7) the prediction of athletic coping skills inventory, leg muscle strength, agility, torso flexibility, eye-foot coordination, leg muscle power with the idan dollyo chagi tae kwon do kyorugi learning result. This research employed the descriptive approach with the methodology correlational. The population of the research in the tae kwon do players age group 15-20 years under 54 kg class Banyumas district, as many as 27 players. The sampling technique was saturated sampling, the size of the samples taken are as many as 27 players. Data analysis technique used technique correlation analysis. To find connectivity (whereabouts of prediction) between predictor variables with criterion variable that is done with correlation analysis product moment. The results of this research showed that when the factors of athletic coping skills inventory, leg muscle strength, agility, torso flexibility, eye-foot coordination, leg muscle power simultaneously having the correlation with the idan dollyo chagi tae kwon do kyorugi learning result, soit will be the happen increased of idan dollyo chagi tae kwon do kyorugi of 0.045 every increase in a rating score of athletic coping skills inventory, 0.037 every increase of leg muscle strength, 2.059 every increase of agility, 0.106 every increase of torso flexibility, 0.353 every increase of eye-foot coordination, 0.001 every increase of leg muscle power.